NIKAIA’DAN YENİ YAZITLAR VII - ÖZTÜRK, HÜSEYİN SAMİ (My University, 2018)
Makalede Nikaia antik kentinin teritoryumunda bulunan 8 yeni yazıtı tanıtılmaktadır: 1) Yerel bir kült derneğininZeus Patrikos’a adağı, 2) Sosybios’un adı bilinmeyen bir tanrıya adağı, 3) Iulius’un beslemelerinin mezarı, 4)Arkesialos’un kardeşi ve eşinin mezarı, 5) Arkesialos’un ve Theokrate’nin babaları ile annesi Asklepiodote’ninmezarı, 8) Philoteos ile eşinin mezarı, 7) Diokles ile eşi Rufina’nın mezarı, 8) Platon’un mezarı. Roma İmparatorlukÇağı’na tarihlenen bu yazıtlar, Bilecik bölgesinden toplanmıştır.

This paper introduces a compilation of 8 unpublished inscriptions found in the territory of the Nicaea: 1) A votive offering of a local cult associations to Zeus Patricus, 2) A votive offering of Sosybios to the unknown God, 3) The grave of Iulius’ feedings, 4) The grave of Arcesilaos’ brother and his wife, 5) The grave of Arcesilaos and Theocrate’s father and their mother Asclepiodote, 6) The grave of Philoteos and his wife, 7) The grave of Diocles and his wife Rufina, 8) The grave of Plato. The inscriptions dating to Roman Imperial Period were gathered from Bilecik region.
NEW INSCRIPTIONS FROM NIKAIA VII
Keywords: Arkeoloji